Factors Affecting Adoption of The Inventory Management Application of Jetion Solar (Thailand) Company Limited - Roongroje, Sarita; Promyoo, Taweep (Journal of Innovation and Management, 2020)
The objective of this research is to study the level of acceptance of the use of inventory management applications and to study the factors that affect the acceptance of the use of inventory management applications of Jetion Solar (Thailand) Co., Ltd. It is a quantitative research. Data was collected from 219 employees of Jetion Solar (Thailand) Co., Ltd. The questionnaires that passed validity checks and confidence values. Percentage, mean, standard deviation, and hypothesis testing by using multiple regression analysis, the research found that technology acceptance factors have a significant effect on the acceptance of the use of inventory management applications that .05 The hypothesis testing can be summarized as follows: perceived independent variables that are useful for use (x1) affect the most according to the acceptance of the use of inventory management applications ( ) followed by perceived ease of use (x2), attitude towards usage (x3) and intention usage behavior (x4) respectively, can explain the acceptance of use of the app Inventory management application of Jetion Solar (Thailand) Co., Ltd. is 63.0%, as shown in the following equation.